Setting research priorities for preconception care in low- and middle-income countries: aiming to reduce maternal and child mortality and morbidity - Dean, Sohni (2013)
Preconception care means providing care before pregnancy is established. Women and couples of reproductive age are generally unaware of the effects that their own health conditions and health-related behaviors may have on the fetus during pregnancy. Although antenatal care is set in the maternal, newborn, and child health (MNCH) continuum [1], it neglects the most critical time of embryonic development, which often occurs before a woman even knows she is pregnant [2]. The evidence increasingly points to earlier care before pregnancy to improve women´s health, and better pregnancy outcomes for the mother and newborn.